Relative Bioavailability of Three Newly Developed Albendazole Formulations: a Randomized Crossover Study with Healthy Volunteers - Rigter, I. M. (American Society for Microbiology, 2004)
This study of healthy volunteers shows that the relative bioavailability of albendazole formulations that use arachis oil-polysorbate 80 or hydroxypropyl-β-cyclodextrin as an excipient was enhanced 4.3- and 9.7-fold compared to the results seen with commercial tablets. Administration of macrogol suppositories did not result in measurable plasma concentrations of albendazole sulfoxide.